2015
DOI: 10.1016/j.matlet.2014.09.128
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in zirconium-doped aluminide coatings

Abstract: a b s t r a c tThe microstructure of the zirconium doped aluminide coating deposited on the nickel substrate by the CVD method is presented. TEM analysis proved that the ß-NiAl and the γ 0 -Ni3Al are the main phases of the deposited coating. Some dislocations in the nickel substrate and in the coating were observed. The cross section chemical composition examination revealed, that the coating was formed via the inward aluminum diffusion and the outward nickel diffusion. SEM analysis revealed small zirconium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…Simultaneously, no Hfrich inclusions nor intermetallic phases like for instance Hf 3 Ni 7 , HfNi 3 , Hf 2 Ni 7 or Ni 2 AlHf, suggested by other authors [17,26] were noted. Similar results have been obtained for zirconium modified aluminide coatings deposited on pure nickel by the CVD method [32]. Also in that case only Zr phase (heksagonal structure with cell parameters: a¼ 3.232 nm and c¼ 5.147 nm) precipitates were found.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Simultaneously, no Hfrich inclusions nor intermetallic phases like for instance Hf 3 Ni 7 , HfNi 3 , Hf 2 Ni 7 or Ni 2 AlHf, suggested by other authors [17,26] were noted. Similar results have been obtained for zirconium modified aluminide coatings deposited on pure nickel by the CVD method [32]. Also in that case only Zr phase (heksagonal structure with cell parameters: a¼ 3.232 nm and c¼ 5.147 nm) precipitates were found.…”
Section: Discussionsupporting
confidence: 86%
“…Also in that case only Zr phase (heksagonal structure with cell parameters: a¼ 3.232 nm and c¼ 5.147 nm) precipitates were found. Zirconium particles were found along grain boundaries at the top surface of the β-NiAl phase [32], whereas hafnium inclusions, observed in the present research are predominantly distributed uniformly inside the β-NiAl phase grains with only occasional presence of such precipitates at the β-NiAl grain boundaries.…”
Section: Discussioncontrasting
confidence: 45%
“…The solubility of the Zr element in the NiAl phase is still unknown, but the diameter of the zirconium atom is much larger than the interplanar spacings of the β-NiAl phase, so it is hard to dissolve much Zr in the NiAl phase. It is estimated that 0.2-0.4 at.% Zr could be dissolved in the aluminide coating [6]. Some research showed that Zr tended to segregate around the NiAl grain boundary as Zr particles or combine with other elements in the form of compounds like Ni7Zr2, NiAl-Zr, or Al5Ni2Zr, etc.…”
Section: The Microstructure Of the Zr-doped Pt-modified Aluminide Comentioning
confidence: 99%
“…Also, there is less β phase transformed into γ' phase in the Zr-doped, Pt-modified aluminide coating, which means that less compressive stress would be formed in the coating and scale. In addition, Zr is reported to aid in increasing the creep resistance and lowering the internal stress [6]. When the internal stress in the alumina layer is too high, it will lead to crack and even spallation of the alumina scale.…”
Section: The Effect Of Zr On the Oxidation Resistance Of The Pt-modifmentioning
confidence: 99%
See 1 more Smart Citation